ANALISIS PENGELOLAANf ASET TANAH MILIK PEMERINTAH DAERAH KOTA PAGAR ALAM - Ramadhani, Albareyzi; Anwar, Faizal; Darmi, Titi (Universitas Muhammadiyah Bengkulu, 2022)
The problem that exists in the management of land assets owned by the Regional Government of Pagar Alam City is the large number of government-owned lands that have not been certified, then there is still land that overlaps with the community, this makes it important to manage good land assets belonging to the City Government of Pagar Alam. The formulation of the research problem is to find out how the managementf of land assets owned by the Regional Government of Pagar Alam City and what factors support and hinder thef implementation of this management. The purpose of this study was to determinef the managementf of land assets owned by the Regional Governmentf of Pagarf Alam City as well as the supporting factors and management constraints. Researchers used a qualitative descriptive research method. In this study, the data used are primary and secondary data obtained through interview, observation, and documentation techniques. Furthermore, this study uses data analysis techniques from miles and huberman. The management of land assets belonging to the Regional Government of Pagar Alam City which is carried out by the Regional Finance Agency of Pagar Alam City in the management inventory carried out has been optimal considering the land asset data is quite complete. Unlike the case with certification and also utilization where researchers can conclude that the management is still not optimal, it can be seen from the existence of uncertified land, maintenance that is not running and utilization of land assets is still very minimal where there is still land that has not been certified. there are still many abandoned and abandoned land assets. The supporting factor for the management of land assets owned by the Pagar Alam City Government is the existence of an SOP or standard operating procedure that helps in the implementation of management, as well as good communication. Meanwhile, the inhibiting factor can be seen from the attitude of the related officers as policy implementers who are still not good enough as the apparatus. In addition, there is still a lack of supporting facilities for land guardrails, which often creates problems between the government and people who like to recognize rights to land owned by the government.Keywords: Management, Assets, Land